An Analysis of Basic Education Policy Implementation (MI/SD Levels) - Zulkarnain, Zulkarnain; Zainudin, Zainudin; Yulita, Ona; Rahayu, Yusri (Universitas Pahlawan Tuanku Tambusai, 2022)
Policy analysis does not stop at using various assessment methods to generate and transform information. This study aims to analyze the implementation of basic education policies (SD/MI levels). The research method used in this study is a qualitative study through literature/document studies, namely studies conducted by reviewing documents from both private and public documents such as scientific articles and applicable regulations. In this study, the author takes an inventory of various sources both from books, journals, information from the internet, and related regulations. Various information from the relevant references are then reviewed and analyzed. Policy arguments which are a means to conduct debates on public policy issues, have a minimum of six elements, namely: (1) Policy-relevant information, (2) policy claims, (3) Justification, (4) Support, ( 5) Rebuttal, and (6) Conclusion. Policy arguments are made to serve as guidelines for action, directing activities in educational organizations to achieve the goals that have been set, increasing the validity (dialectical function), optimizing truth conclusions, inviting and influencing other parties to accept arguments.